HUBUNGAN KADAR MAGNESIUM DENGAN VOLUME HEMATOMA DAN DERAJAT KLINIS PASIEN PERDARAHAN INTRASEREBRAL - Bhetaria Santoso,* Amiruddin Aliah,* Susi Aulina* (Neurona Majalah Kedokteran Neuro Sains, 2020)
INTRODUCTION HIGH SERUM MAGNESIUM LEVELS AT HOSPITAL ADMISSION ARE ASSOCIATED WITH A SMALL VOLUME OF INCOMING HEMATOMA WITH A LOWER NATIONAL INSTITUTES OF HEALTH STROKE SCALE NIHSS SCORE